2014
DOI: 10.1210/en.2013-1646
|View full text |Cite
|
Sign up to set email alerts
|

The PTTG1-Binding Factor (PBF/PTTG1IP) Regulates p53 Activity in Thyroid Cells

Abstract: The PTTG1-binding factor (PBF/PTTG1IP) has an emerging repertoire of roles, especially in thyroid biology, and functions as a protooncogene. High PBF expression is independently associated with poor prognosis and lower disease-specific survival in human thyroid cancer. However, the precise role of PBF in thyroid tumorigenesis is unclear. Here, we present extensive evidence demonstrating that PBF is a novel regulator of p53, a tumor suppressor protein with a key role in maintaining genetic stability, which is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 61 publications
(86 reference statements)
1
46
1
Order By: Relevance
“…RAD6A binding proteins, several well-established RAD6 binding proteins were found, including RNF20 and RNF40 (9,(13)(14)(15), H2B (9,15), and p53 (16)(17)(18), strongly supporting the reliability of our proteomic data (Fig. 1C).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…RAD6A binding proteins, several well-established RAD6 binding proteins were found, including RNF20 and RNF40 (9,(13)(14)(15), H2B (9,15), and p53 (16)(17)(18), strongly supporting the reliability of our proteomic data (Fig. 1C).…”
Section: Resultssupporting
confidence: 85%
“…4B). As RAD6 is an E2 ubiquitin-conjugating enzyme that is tightly involved in the regulation of protein degradation (12,16,18,20,(26)(27)(28)(29), we next examined the effect of RAD6 on PSMF1 ubiquitination. Under X-ray irradiation conditions, RAD6 depletion significantly blocked the ubiquitination of PSMF1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed however that Mdm2‐mediated turnover of mutant p53 is ineffective in tumors due to binding of heat‐shock proteins and the inability of p53 mutant protein to transactivate Mdm2 . Recently, we showed that the action of PBF on p53 in thyroid cells appeared to be Mdm2‐dependent as the inhibitor nutlin‐3, which blocks binding of Mdm2 to p53, abrogated the ability of PBF to diminish p53 stability . Based on these observations our current model is that elevated PBF levels in colorectal tumors are unable to promote destabilization of mutant p53 due to diminished regulation by the E3 ligase Mdm2.…”
Section: Discussionmentioning
confidence: 84%
“…It is unlikely however that PBF is functioning as an E3 ligase such as Mdm2 to promote p53 ubiquitination as it does not contain a well‐defined domain with either ubiquitin‐conjugating (UBC) or E3 ligase activity. Instead, we envisage that PBF may have a role in promoting the interaction of p53 with proteins known to alter its ubiquitination or acetylation status, such as Mdm2 , HDAC1 , PCAF or Tip50 . Importantly, we were also able to show that binding of PBF to p53 had functional consequences, with reduced transactivation in p53 reporter assays and increased survival of irradiated HCT116 cells, as well as altered mRNA expression for p53‐regulated genes in both PBF‐transfected and PBF‐depleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Its best described role however lies in binding the sodium iodide symporter NIS and regulating its subcellular localization within thyroid cells (20, 21). PBF also interacts with the tumor suppressor p53 (18, 22) and the protein kinase Src (23). In particular, PBF is a phospho-protein and interaction with Src elicits phosphorylation at tyrosine (Y) residue 174.…”
mentioning
confidence: 99%